Revitalizing Marketing Strategies Through the Use of Artificial Intelligence: Analysis of the Effect of Personalization, Market Data Analysis, and Campaign Automation on Sales Conversions - Suryathi, Wayan; Wayan Rena Mariani, Ni (Takaza Innovatix Labs Ltd., 2024)
This article examines how artificial intelligence (AI) is used in marketing at PT. Tirta Investama. It uses multiple linear regression analyses to study the impact of three key strategies on sales conversion. These strategies are: